Heart rate variability in young men: Effect of overweight and physical inactivity (2015)
Physical inactivity, overweight and obesity are factors that contribute to the development of chronic non-communicable diseases, which cause 35 million deaths each year, equivalent to 60% of all deaths worldwide [1]. Regular aerobic physical activity results in health benefits and reduces the risk of mortality [2]. These benefits include the prevention of diseases like diabetes, hypertension, obesity, and cancer [1]. Heart rate variability (HRV) is measured as heart rate oscillations occurring between beats, and allows the non-invasive study of autonomic modulation of cardiovascular function. HRV is used as an indicator of health status [3, 4] and predicts adverse cardiac events and mortality both in healthy people [5] and in those with cardiovascular disease [6, 7]. The aim of this study was to analyze the behavior of HRV in young men with different body mass index (BMI) and level of physical activity. Methods Descriptive, analytical cross-sectional study. From short heart rate records (5 minutes) in rest, time and frequency domain HRV analysis were performed, in young men between 18 and 25 years, distributed in three groups: a) 11 physically inactive men with normal BMI; b) 10 physically inactive with BMI . 25 kg/m2; c) 12 aerobically trained men with normal BMI. Results Aerobically trained subjects had higher heart rate variability with respect to the physically inactive as determined by time domain analysis (lower heart rate; higher RR interval, rMSSD, and pRR50) and by frequency domain analysis (higher HF and LF; lower LF/HF). Within physically inactive subjects, it was observed that the body mass index is negatively correlated with HF and total fractal power (R = -0448, and -0566, respectively). Conclusion The results suggest that subjects with regular long-term aerobic training have increased HRV, compared to physically inactive subjects. In sedentary men, BMI was inversely correlated to HRV. Physical inactivity and overweight seem to have a negative and apparently synergistic effect on HRV. It is recommended to evaluate the usefulness of HRV in rest in monitoring intervention programs for controlling body weight. © 2015 by Nova Science Publishers, Inc. All rights reserved.